Mortality and cause of death in physical activity and insufficient physical activity participants: a longitudinal follow-up study using a national health screening cohort - Chanyang Min; Dae Myoung Yoo; Jee Hye Wee; Hyo-Jeong Lee; Soo Hwan Byun; Hyo Geun Choi (BMC, 2020)
Abstract Background Few studies have examined the association between physical activity (PA) and various causes of mortality in Korea. The aim of our study was to evaluate mortality and causes of death between PA and insufficient PA using Korean national cohort data. Methods The health screening cohort data from the Korean National Health Insurance Service-National Sample Cohort from 2009 to 2015 were used. 'PA' was determined if participants walked or performed moderate-intensity activity ≥5 d/week for ≥30 min, or vigorous-intensity activity ≥3 d/week for ≥20 min. Other participants were classified as 'insufficient PA'. The PA and insufficient PA groups were matched by age, sex, income, and region of residence in a 1:1 ratio. Causes of death were classified into 13 categories. Crude and adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for all mortality rates were analyzed using a stratified Cox proportional hazard model. Age, sex, income, and region of residence were stratified. Subgroup analyses were performed according to age, sex, and obesity status. The odds ratio according to the causes of death was calculated by the chi-square test. Results The adjusted HR for mortality in the PA group was 0.85 (95% CI = 0.82-0.88). In subgroup analyses according to age, sex, and obesity status, results were consistent with the main findings in < 60-year-old females, ≥ 60-year-old males and females, and in all subgroups by obesity. The death rate by neoplasm, mental diseases, neurologic disease, circulatory disease, respiratory disease, digestive disease, abnormal finding, and trauma were lower in the PA than the insufficient PA group. Conclusions These results suggest that PA is inversely associated with mortality caused specifically by diseases reflected by mental, respiratory, cancer, and cardiovascular conditions. Additionally, PA is inversely associated with mortality compared to insufficient PA in all obesity status.